2017
DOI: 10.21153/jtlge2017vol8no1art657
|View full text |Cite
|
Sign up to set email alerts
|

Student voice and influence on employability in Australian higher education

Abstract: Higher education institutions are increasingly focussed on improving the capacity and potential of their graduates to gain employment. Attempts to develop employability skills through both mainstream and extra-curricular activities create new demands and expectations for students. Despite these demands, little attention has been given to student voice and influence in the employability sphere. Furthermore, the specific role of student unions in improving employability has been marginalised in Australian resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Such low engagement often results in late career exploration by some students (Monteiro et al 2021). Moreover, students who need career services the most (i.e., students from low social-economic status, as well as minority, rural, and disabled students) tend not to use careers services more frequently due to lack of time, as well as work and other commitments (Andrewartha and Harvey 2017;Amoroso and Burke 2018;Jackson and Edgar 2019). However, those students who engage with the careers services often find them helpful with their traditional roles (i.e., help with CV preparation, application letters, interview preparations, career counselling, job search, processing of internships, and arranging job fairs) (Conroy et al 2020;Chin et al 2018).…”
Section: Learning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such low engagement often results in late career exploration by some students (Monteiro et al 2021). Moreover, students who need career services the most (i.e., students from low social-economic status, as well as minority, rural, and disabled students) tend not to use careers services more frequently due to lack of time, as well as work and other commitments (Andrewartha and Harvey 2017;Amoroso and Burke 2018;Jackson and Edgar 2019). However, those students who engage with the careers services often find them helpful with their traditional roles (i.e., help with CV preparation, application letters, interview preparations, career counselling, job search, processing of internships, and arranging job fairs) (Conroy et al 2020;Chin et al 2018).…”
Section: Learning Methodsmentioning
confidence: 99%
“…Ergun and Sesen (2021) took note of the fact that there has been limited empirical research on students' perception of their employabil-ity. Andrewartha and Harvey (2017) observed that students' views and perceptions have largely been ignored in the employability arena. Academic researchers have not pursued research on students' views with the same vigour as they have done on employers' (Higdon 2016;Tymon 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ergun & Sesen [26] takes note of the fact that there has been limited empirical research on students' perception of their employability [1]. Andrewartha & Harvey [27] observes that students' views and perceptions have largely been ignored in the employability arena [1]. Academic researchers have not pursued research on students' views with the same vigour as they have done on employers' [1,22,28].…”
Section: Annals Of Social Sciences and Management Studiesmentioning
confidence: 99%